2022
DOI: 10.1126/sciadv.abm2054
|View full text |Cite
|
Sign up to set email alerts
|

Parallel functional subnetworks embedded in the macaque face patch system

Abstract: During normal vision, our eyes provide the brain with a continuous stream of useful information about the world. How visually specialized areas of the cortex, such as face-selective patches, operate under natural modes of behavior is poorly understood. Here we report that, during the free viewing of movies, cohorts of face-selective neurons in the macaque cortex fractionate into distributed and parallel subnetworks that carry distinct information. We classified neurons into functional groups on the basis of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…SDF was normalized as the normalized firing rate response by subtracting the baseline response and then dividing it by the absolute difference between the baseline and maximum response of the neuron. Face selectivity index (FSI) ( 53 , 54 ) was calculated from the mean baseline-subtracted responses to familiar faces ( X faces ) and familiar nonface images ( X nonface ) as: FSI = ( X faces – X nonface )/(| X faces | + | X nonface |). In case FSI > 1, FSI = 1.…”
Section: Methodsmentioning
confidence: 99%
“…SDF was normalized as the normalized firing rate response by subtracting the baseline response and then dividing it by the absolute difference between the baseline and maximum response of the neuron. Face selectivity index (FSI) ( 53 , 54 ) was calculated from the mean baseline-subtracted responses to familiar faces ( X faces ) and familiar nonface images ( X nonface ) as: FSI = ( X faces – X nonface )/(| X faces | + | X nonface |). In case FSI > 1, FSI = 1.…”
Section: Methodsmentioning
confidence: 99%
“…It is interesting to contrast the present findings with recent work in which the time course of face patch neurons was compared to whole-brain fMRI activity during periods of naturalistic visual experience ( 24 , 25 ). Those previous studies did not measure the simultaneous covariation of spontaneous signals but rather the driven covariation of externally visual inputs.…”
Section: Discussionmentioning
confidence: 58%
“…We next asked to what extent neurons within a local population, in a sense occupying the same voxel, share their fMRI coupling with networks across the brain. This question was motivated, in part, by recent findings that during periods of natural visual behavior, neighboring face patch neurons differ markedly in their brain-wide fMRI coupling ( 24 , 25 ). However, in contrast to naturalistic viewing conditions, we found that the spatial pattern of resting-state coupling was highly shared among neurons in a local population, aside from the polarity inversion exemplified in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, movies have been found to have high intersubject correlation and reliability (Hasson, Furman, et al, 2008;Yang et al, 2021), holds subjects' attention (Hasson, Landesman, et al, 2008), and improves compliance related to motion and wakefulness (Vanderwal et al, 2015). Naturalistic movies are also an ideal stimulus for multimodal data sets and may be useful in linking responses across levels (Park et al, 2017(Park et al, , 2022 and species (Mantini et al, 2012).…”
Section: Introductionmentioning
confidence: 99%